Community Participation in the Formation of Regional Regulations to Realize the Indonesian Welfare State - Hindiawati , Wahyu (PT. Hafasy Dwi Nawasena, 2024)
The 1945 Constitution of the Republic of Indonesia (UUD 1945), as the basic law, is a general agreement (consensus) of citizens regarding basic norms (grundnorm) and basic rules (grundgesetze) in state life. This agreement primarily concerns shared goals and ideals. Sovereignty is held by the people. People's active participation includes, among other things, political activities and government activities. Active participation from the people includes, among other things, decision making, implementation and monitoring of policies. It is from this large participation of the people that can create a government of the people, by the people, and for the people in order to realize prosperity. This research uses normative legal research methods or what is usually called normative legal research. Normative legal research is research carried out by analyzing or studying the laws and regulations that apply or are applied to a particular legal problem. The results and conclusions of this research are as follows: 1) In the formation of regional regulations, community aspirations are needed and of course balanced with community involvement, including 1. Involvement in drafting regional regulations; 2. Involvement in the process of discussing regional regulations; 3. Involvement in the implementation of regional regulations; 2) Implementation of regional regulations in realizing prosperity, namely regional regulations can be interpreted as community services at the provincial, district/city level. The government must be able to create development of community creativity in order to achieve shared prosperity.